ظواهر أسلوبية بين الشعر والقرآن من خلال شرح ديوان الحماسة للمرزوقي - يعقوب, قادة (université de bouira, 2016)
الملخص : يعرض هذا المقال مجموعة من الظواهر الأسلوبية المشتركة بين الشّعر العربي القديم والقرآن الكريم،درسها المرزوقي في شرح ديوان الحماسة،واستعمل في تحليلها الشاهد من الآيات القرآنية ليبرهن على صحةّ استنتاجاته،ويثبت اشتراك الشّعر العربي القديم والقرآن الكريم في ظواهر أسلوبية مثّلت سنن العرب في القول البليغ،كما يُناقش المقال دور شارحي الشّعر،ومفسّري القرآن في إمداد التحليل الأسلوبي بالإجراءات التطبيقية التي توضّح مبدأي الاختيار والإنزياح المحددين للظاهرة الأسلوبية،وقد أبان كلّ ذلك عن سبل تلقي النّص الشّعري والنّص القرآني،والعلاقة الرابطة بينهما،كما أفصح، باستخدام المقارنة الأسلوبية،عن كيفية تحوّل الاستعمال اللّغوي إلى ظاهرة أسلوبية،والسياقات التي تفرض هذا التحوّل. Abstract Stylistic Phenomena between Poetry and Qur’an through the Explanation of “Diwan Al-Hamassa” by Al-Marzugui This paper represents a number of stylistic phenomena shared by ancient Arabic poetry and the Holy Qur’an studied by Al-Marzugui in “Sharh Diwan Al-Hamassa”. He illustrated his analysis with Qur’anic verses to demonstrate his results accuracy and to prove that ancient Arabic poetry and the Holy Qur’an share stylistic phenomena which reflect the Arabs’ habit in pronouncing rhetorical utterances. This paper also discusses the poetry interpreter’s role and that of the exegete of Qur’an in providing stylistic analysis with practical techniques which clarify the two principles option and deviation, -the two principles determining the stylistic phenomenon. All that has shown the ways of poetic and Qur’anic texts reception and the relationship between these two texts ; it has also shown, through comparative stylistics, how the linguistic usage has been transformed into a stylistic phenomenon as well as the contexts which impose this transformation.
Keywords: الأسلوبية - الشعر والقرآن - المرزوقي